Tree of life theory, on how homo sapiens improve their cognitive system to consciousness - De Carvalho Azpiazu, Jose Luis (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
The consciousness is a natural product of evolution, this paper will present a theory based on Alkaloids having an important role over the process due it´s crosstalk effect. This would permit the complexification of the information structures processed by early gender Homo brains, allowing by natural selection consciousness to arise on effective forms.